The legacy of a standard of normality in child nutrition research - Austin Sandler (Elsevier, 2021)
Anthropometric evaluation of children is among the most vital and widely used instruments of public health and clinical medicine. Anthropometry is used for establishing norms, identifying variations, and monitoring development. Yet the accurate assessment of physical growth and development of children remains a perpetually beleaguering subject. This paper focuses on the evolution of anthropometry as a science and its associated measurements, indices, indicators, standards, references, and best practices. This paper seeks to clarify aspects of the assessment of child growth, explores the historical trajectory of the study of anthropometry and its contemporary limitations, and contributes to the debate surrounding references and standards, and the applicability of international anthropometric standards to an individual's health. Among its findings is a surprisingly nonlinear and contested record of events, up to and including leading contemporary practices and datasets. It contextualizes the legacy of child malnutrition studies in a broad framework, including the linkage between the early eugenics movement and contemporary notions of a "normal" child, the interpersonal and intuitional competition to become the preeminent child growth authority, the obfuscated distinction between reference growth charts and standards of growth, and the hidden consequences of universal growth standards that no longer reflect any observable populations.